The Twin Crises: Determinants of Banking and Currency Crises in the Turkish Economy. Issue 1 (2nd January 2016) - Ari, Ali; Cergibozan, Raif
ABSTRACT: Several twin crises occurred in the Turkish economy in the last three decades. In this article, we aim to analyze the link between banking and currency crises and to illustrate the essential determinants of these twin crises by developing a multivariate logit model for the period 1990–2013. The empirical findings show that Turkish currency crises are mainly due to excessive fiscal deficits, rises in short-term external debt, overvaluation of Turkish lira, and external adverse shocks; banking crises are primarily caused by excessive money supplies and bank short positions. The empirical findings also indicate that banking crises lead to currency crises, and vice versa.